Mastering your inner critic ... and 7 other high hurdles to advancement : how the best women leaders practice self-awareness to change what really matters - Brady, Susan (Susan McKenty) (McGraw-Hill, 2019)
Filled with inspiring anecdotes from accomplished women at various stages in their careers, as well as proven strategies any woman can use in the workplace, this unique guide helps you confront your inner critic, face your hurdles head on, and achieve the goals that really matter to you. --